Control biológico de Anagyrus pseudococci Giraul sobre la cochinilla de los cítricos, Planacoccus citri Risso - Ceballos Trejo, Kevin David (2024)
The citrus activity worldwide is one of the most representative, given its contribution to the market with exquisite and extremely attractive fruits due to their variety, flavor, and nutritional properties, also being used for medicinal purposes in case of fevers, colds, stomach diseases and deficiency. of vitamin C; Due to its importance, producers find it necessary to take care of their crops not only by fertilizing carefully, but also by implementing a pest control system that reduces the environmental impact. The citrus mealybug, Planococcus citri Risso is one of the pests that causes the most damage to the Citrus genus, finding accommodation in the plant from the stem to the fruit itself; When considering the biological control of pests as a means for their eradication, the introduction of natural enemies such as the parasitoid Anagyrus pseudococci Giraul is suggested, which acts by laying eggs inside the pest insect, immobilizing it a few weeks after settling on its host and subsequently causing its death. The use of biological control on the citrus scale insect P. citri Risso allows raising awareness among farmers about the importance of reducing the application of pesticides that leave chemical residues in the fruit and alter the ecosystem, which usually happens with synthetic insecticides; A. pseudococci Giraul has demonstrated its effectiveness in the biological control of pests in citrus crops, being marketed in European countries such as Spain where the product is distributed in jars containing pupae and adult insects with the respective indications for their release. in the orchards.